Solve the proportion.

s+1/4 = 4/8
s=

Answers

Answer 1
Answer:

Answer:

8 = 16

Step-by-step explanation:

1/4  =  4 /8

 

Cross multiply:

1 * 8 = 4 * 4

Simplifying

1 * 8 = 4 * 4

Multiply 1 * 8

8 = 4 * 4

Multiply 4 * 4

8 = 16

Solving

8 = 16


Related Questions

Plz halp i need to get this right.
which of the following statements best describes the effect of replacing the graph of y = f(x) with the graph of y = f(x) − 11? (5 points) the graph of y = f(x) will shift up 11 units. the graph of y = f(x) will shift right 11 units. the graph of y = f(x) will shift left 11 units. the graph of y = f(x) will shift down 11 units.
Use the distributive property to expand this equation please2/3 (18x + 6z)
What is 4 over 10 in simplest form
If the probability of an event is 26%, what is the probability of its complement occurring?

Select all that apply.Which of the following are equivalent?


0.4
40%
4%
2/5

Answers

4% is not equivalent to 40%
0.4 is equivalent to 40%.  Just move the decimal two places to the right.
2/5 is equivalent to 0.4,  which in turn is equivalent to 40%.  2 divided by 5=0.4
The answers are all but 4%

Answer:

All but 4%

Step-by-step explanation:

2/5 - 1/4 show your work

Answers

2/5-1/4

8/20 - 5/20

(8-5)/20

= 3/20


I hope that's help ! if you have question please ask

2/5-1/4

2/5=8/20

1/4=5/20

8/20-5/20=3/20
The answer to the problem is3/20

Triangle inequality theorem

Answers

The triangle inequality theorem is an important part of geometry in order to mention the dimension of the sides of a triangle clearly.

What is triangle inequality theorem?

The triangle inequality theorem states that, the sum of the length of two sides must be greater than the length of the third side of that triangle.

Here, three sides of this triangle ABC are AB, BC, and CA.

Therefore, as per the triangle inequality theorem:

(Length of AB + length of BC) must be greater than the length of CA.

Therefore, (AB + BC) > CA.

(Length of BC + length of CA) must be greater than the length of AB.

Therefore, (BC + CA) > AB.

(Length of AB + length of CA) must be greater than the length of BC.

Therefore, (AB + CA) > BC

For an example, if we are running in a triangular shaped track, then it can be easily understandable.

Now, if we start running from the point A, then to reach the point B the shortest path will be the straight line AB.

Instead of that, if we go to the C point at first and then reach the point B, then we will travel more distance.

Similarly, starting from the other points, we will get the same results.

Learn more about triangular inequality theorem here: brainly.com/question/18345497

#SPJ2

Triangle inequality theorem states that the sum of any two sides of a triangle must be greater than the third side because if not you don't have a triangle.

The diameter of a quarter is 2.4 cm. You trace around the edge of the quarter on a sheet of paper. What is the area of the circle on the paper? Use 3.14 as an approximation for π. Round your answer to the nearest tenth.

Answers

The area of the circle on the paper is 4.5 cm when traced around the edge of the quarter on a sheet of paper.

What is the area of the circle?

The area of the circle is equal to the product of the square of the radius of the circle and pi.

A = πr²

where 'r' is the radius of the circle

The diameter of a quarter is 2.4 cm. You trace around the edge of the quarter on a sheet of paper.

The area of the circle on the paper = πr²

Here r = (diameter of a quarter)/2 = 2.4/2 = 1.2 cm

The area of the circle on the paper = π(1.2)²

The area of the circle on the paper = π × 1.44

The area of the circle on the paper = 4.5238

Round the answer to the nearest tenth.

The area of the circle on the paper = 4.5 cm

Thus, the area of the circle on the paper is 4.5 cm

Learn more about the Circumference and area of the circle here:

brainly.com/question/19794723

#SPJ1

Answer:its 4.5

Step-by-step explanation:

Please help me!!!

-x + (−3) = x + 3 ​

Answers

Step-by-step explanation:

-x - 3 = x + 3

Solving like terms

-3 - 3 = x + x

-6 = 2x

-6 / 2 = x

-3 = x

Answer:

-3

Step-by-step explanation:

You are trying to solve for x in this situation. So the first thing you want to do is choose a side (it doesn't matter in this situation bc there is an x on either side of the =) and isolate the x.

**I'm going to choose the left side cause why not** Add the -3 to both sides to get -x by itself:

-x + (−3) = x + 3

-x -3= x+3

* quick side note,  when you add a negative number to a positive, it has the same effect as subtracting

-x=x+6

Now -x is by itself but there is still another x, so combine like terms again:

-2x=6

Now simplify by dividing -2 to both sides:

x=-3

A fish tank contains 18 goldfish and 22 guppies. If you randomly select 2 fish, what is the probability that they are both goldfish?

Answers

18 goldfish+22 guppies=40 total
18/40 are goldfish and 22/40 are guppies
Odds that 1 goldfish is chosen at random is 18/40 or 9/20 when simplified so odds that 2 goldfish are chosen at random is 9/20×9/20=81/400 or 20.25%